Striatal dopaminergic lesions contributed to the disease severity in progressive supranuclear palsy - Chen, Ming-Jia; Lu, Jia-Ying; Li, Xin-Yi; Jiao, Fang-Yang; Zuo, Chuan-Tao; Wang, Jian; Liu, Feng-Tao; Yang, Yu-Jie (Frontiers in Aging Neuroscience, 2022)
Background Reduced dopamine transporter (DAT) binding in the striatum has been reported in patients with progressive supranuclear palsy (PSP). However, the relationship between striatal dopaminergic lesions and the disease severity of PSP remains to be explored. Objective To investigate the contributions of striatal dopaminergic lesions to the disease severity of PSP. Methods One hundred patients with clinically diagnosed PSP were consecutively enrolled in this study. The disease severity was systemically assessed using the PSP rating scale (PSPrs), and the dopaminergic lesions were assessed using the 11C-N-2-carbomethoxy-3-(4-fluorophenyl)-tropane positron emission tomography (11C-CFT PET) imaging. To explore the correlations between striatal DAT bindings and the disease severity, both the region-wise and voxel-wise analysis were adopted. Partial correlations and multiple linear regressions were performed to investigate the contribution of striatal dopaminergic lesions to the disease severity in PSP. Results Sixty-three patients of PSP with Richardson’s syndrome (PSP-RS) and 37 patients with PSP-non-RS were finally included. The disease severity in PSP-RS was much heavier than that in the PSP-non-RS. The DAT bindings in the caudate and anterior putamen correlated significantly with the PSPrs total scores, mainly in the domains of history, mentation, bulbar and ocular motor symptoms. The striatal DAT bindings (caudate) contributed significantly to the disease severity of PSP, independent of the motor, cognition, emotion and behavioral dysfunctions. Conclusion Our study highlighted the independent contribution of striatal dopaminergic lesions to the disease severity in PSP.